If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 12) = 3x + 24 Reorder the terms: 2(12 + x) = 3x + 24 (12 * 2 + x * 2) = 3x + 24 (24 + 2x) = 3x + 24 Reorder the terms: 24 + 2x = 24 + 3x Add '-24' to each side of the equation. 24 + -24 + 2x = 24 + -24 + 3x Combine like terms: 24 + -24 = 0 0 + 2x = 24 + -24 + 3x 2x = 24 + -24 + 3x Combine like terms: 24 + -24 = 0 2x = 0 + 3x 2x = 3x Solving 2x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2x + -3x = 3x + -3x Combine like terms: 2x + -3x = -1x -1x = 3x + -3x Combine like terms: 3x + -3x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| y=15+3 | | 16=t(t-6) | | 5y+7y=24 | | 52.5=15x | | 3h=0.3h+0.075 | | y-0.6=-2.4 | | 0.25d+0.5=12 | | z^2-(3+3i)=0 | | 3x^3+16x+5= | | 288(564)=752(x) | | 3/w-14=10 | | -2=x/4+1 | | (3x-2)(6x+12)= | | 4(x+7.5)=40 | | 5x+7=39x-8 | | 35+10+8x=61 | | w+0.625=0.5 | | 24q-64=8q | | 4x-36=2x-12 | | -2+12=m-1 | | 18=18+2x | | log^4(x+2)=log^4(55) | | 12-4x+0.6x^2=11.3 | | 12-4x+0.6x^2=0 | | 5-x/2=21 | | 8x-(5-(4x+7))=26 | | p^2-30= | | x/8+100=300 | | y=-30+16 | | -1.8m-8=0.2m | | -1.8-8=0.2m | | 15-(5x-4)=19-(2x+4) |